Some Observations on the Occurrence of ?-Thalassemia in Mosul (Iraqi Journal of Medical Sciences, 2016)
Background:?-thalassemia is found in Mediterranean, Saudia Arabia, Jordan, Egypt and Yemen. Survey in Iraq showed that ?-thalassemia trait is carried by 4.5-5% of the population.Objective:To determine factors that is associated with thalassemia in Mosul district. Methods: 105 thalassemia blood transfusion dependent children with the age of 2.5–18 years attending Ibn Al-Atheer Teaching Hospital in Mosul city during 2005 were included in this study, 45 healthy subjects served as control. Blood groups, Hb, and PCV were evaluated. SI, TIBC, and TS levels were also determined.Results:The occurrence of homozygous ?-thalassemia is significantly higher in the offspring of first cousin marriages."O" blood group represents a highest percentage (42.8%) among the thalassemic patients. Hb, PCV and TIBC were below the control measurements. Whereas SI and TS were above that of the controls.Conclusions:Consanguinity seems to be increasing the size of the disease due to the limited health education of the parents about the disease.Key words: Thalassemia, Hb, PCV, SI, TIBC, TS
Keywords: Thalassemia; Hb; PCV; SI; TIBC; TS